2014
DOI: 10.1094/phyto-02-14-0047-r
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Resistance to Cercospora sojina Infection Is Reduced by Silicon

Abstract: Frogeye leaf spot, caused by Cercospora sojina, is one of the most important leaf diseases of soybean worldwide. Silicon (Si) is known to increase the resistance of several plant species to pathogens. The cultivars Bossier and Conquista, which are susceptible and resistant, respectively, to frogeye leaf spot, supplied and nonsupplied with Si were examined for the activities of defense enzymes and the concentrations of total soluble phenolics (TSP) and lignin-thioglycolic acid (LTGA) derivatives at 8, 14, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 56 publications
8
22
0
Order By: Relevance
“…The coffee plant recognized the strains in a similar way and was inhibited by H 2 O 2 produced by the plant, which can be demonstrated through increased POX and APX activity in the first hours of infection. Similar results were reported by NASCIMENTO et al (2014), who verified increased POX and PAL enzyme activity in inoculated soybean plants with Cercospora sojina. POX is a pathogenesis related protein and is induced in the host by the presence of pathogens ( VAN LOON et al, 2006).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The coffee plant recognized the strains in a similar way and was inhibited by H 2 O 2 produced by the plant, which can be demonstrated through increased POX and APX activity in the first hours of infection. Similar results were reported by NASCIMENTO et al (2014), who verified increased POX and PAL enzyme activity in inoculated soybean plants with Cercospora sojina. POX is a pathogenesis related protein and is induced in the host by the presence of pathogens ( VAN LOON et al, 2006).…”
Section: Resultssupporting
confidence: 90%
“…In literature, there are a few accounts of alterations in the antioxidant metabolism of infected plants by Cercospora, mainly when it refers to strains that cause different symptoms in coffee plants (NASCIMENTO et al, 2014). When comparing the two C. coffeicola strains (common BE and black BE), the results showed that both strains were able to induce the activity of enzymes in coffee leaves; however, there was variation in the timing of enzymes activation for each strain depending on the enzyme being analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Nascimento et al. (, ) noticed an increase in the susceptibility of soybean plants to FLS when supplied with Si. Deshmukh et al.…”
Section: Introductionmentioning
confidence: 85%
“…Potassium silicate was passed through a cation‐exchange resin (Amberlite IR‐120B, H + form; Sigma‐Aldrich, São Paulo, Brazil) to obtain the monosilicic acid (Ma, Tamai, Ichii, & Wu, ). The Si concentration of 2 mM (+Si) was used to prepare the nutrient solution (Debona et al., ; Nascimento et al., , ) to allow the highest Si uptake by plants during their growth.…”
Section: Methodsmentioning
confidence: 99%